Dose transfer of an oilbased formulation of Metarhizium anisopliae (Hypocreales: Clavicipitaceae) sprays to cotton bollworm in an arena trial - Kpindou, O.D.; Djegui, D.A.; Glitho, I. A.; Tamo, Manuele (2011)
A cotton field was used to set up an arena trial for investigating the dose transfer of oil-based ultra-low-volume sprays of Metarhizium anisopliae (Metchnikoff) Sorokin to the cotton bollworm Helicoverpa armigera (Hübner). Two doses of conidia (75 and 50 g/ha, being 3.75 × 1012 and 2.5 × 1012 conidia/ha, respectively) formulated in 2 litres (70:30, kerosene–peanut oil) were applied using a Berthoud ‘Micro Ulva’ to three groups of larvae of cotton bollworms positioned in three rows downwind of a single spray line. Both the distribution of the droplets and the effect of direct contact with spray droplets were quantified. The mean number of droplets decreased from 416 ( ± 60) droplets per cm2 (line 1; 0.4 m) to 45 ( ± 36) droplets per cm2 (line 3; 5 m). To achieve 50% mortality, >10 and >13 days were necessary for 75 and 50 g/ha, respectively. From day 15, the difference in mortality rates was significant between the two treatments. At line 3 (5 m), at 12 days after application, the mortality rate reached 52% for 75 g/ha and 47% for 50 g/ha. The results are discussed in view of optimizing the application of the biopesticides.